2020
DOI: 10.1098/rstb.2019.0270
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensory communication of aggression: women's fine-tuned neural processing of male aggression signals

Abstract: The current study is the first to examine the central nervous processing of aggression chemosignals within men and women by means of chemosensory event-related potential (CSERP) analysis. Axillary sweat was collected from 17 men and 17 women participating in a competitive computer game (aggression condition) and playing a construction game (control condition). Sweat samples were pooled with reference to donor gender and condition, and presented to 23 men and 25 women via a constant flow olfactometer. Ongoing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 43 publications
2
28
0
1
Order By: Relevance
“…Sniffing one particular molecule expressed in body-odor (Androstadienone) raises levels of cortisol in women ( 43 ), and sniffing a different particular molecule expressed in body-odor (Hexadecanal), blocks aggression in men, but triggers aggression in women ( 44 ). Humans can infer a state of disease in body-odor ( 45 ), and can smell aggression ( 46 ), fear ( 25 ), stress ( 47 ), depression ( 48 ) and happiness ( 26 ). Body-odor also serves as a cue for human kinship ( 22 , 24 ) and influences human mate choice ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sniffing one particular molecule expressed in body-odor (Androstadienone) raises levels of cortisol in women ( 43 ), and sniffing a different particular molecule expressed in body-odor (Hexadecanal), blocks aggression in men, but triggers aggression in women ( 44 ). Humans can infer a state of disease in body-odor ( 45 ), and can smell aggression ( 46 ), fear ( 25 ), stress ( 47 ), depression ( 48 ) and happiness ( 26 ). Body-odor also serves as a cue for human kinship ( 22 , 24 ) and influences human mate choice ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…The paper by Fialová et al [94] follows neatly on that by Pause et al [93] by investigating the odour of winning and losing fighters in mixed martial arts contests, arguably the most aggressive sport in existence. Odours were sampled from fighters about 1 h before and after a contest, and subsequently rated by unfamiliar individuals on several hedonic scales.…”
Section: (F ) Communication Of Emotional State and Diseasementioning
confidence: 99%
“…Pause et al [93] examine odours of people in aggressive contexts. Participants provided odours while being tested in computer games in which responses were linked to overt aggression and resulted in higher testosterone levels, and during game-playing in a control condition.…”
Section: (F ) Communication Of Emotional State and Diseasementioning
confidence: 99%
“…The current science of non-verbal communication via smell is rooted in a longstanding tradition of strictly controlled laboratory experiments focusing on the empirical testing of hypotheses addressing cause-effect relations, using reliable and validated methods and carefully calibrated instruments (for empirical demonstrations, see e.g., Chen and Haviland-Jones, 2000;Regenbogen et al, 2017;Endevelt-Shapira et al, 2018;Quintana et al, 2019;de Groot et al, 2020b;Gomes et al, 2020;Pause et al, 2020 (for recent narrative overviews, see e.g., Loos et al, 2019;Ferdenzi et al, 2020;Havlíček et al, 2020 (for meta-analyses, see e.g., Gildersleeve et al, 2014; de Groot and Smeets, 2017). This approach, with a preference for intrinsic over extrinsic validity, has been the method of choice to build our (psychological) science for decades.…”
Section: Problem I: Small Scale Slow Speedmentioning
confidence: 99%
“…An even less well-known function of smell is social communication (de Groot et al, 2017;Parma et al, 2017;Pause, 2017;Roberts et al, 2020); the topic of this article. Studies have shown that our smells provide others with cues about our identity and gender (Penn et al, 2007), age (Mitro et al, 2012), health (Olsson et al, 2014), and emotions (de Groot et al, 2015;Pause et al, 2020). This form of communication occurs without our voluntary control and generally outside of our awareness, which imbues chemical communication with mystery.…”
Section: Introductionmentioning
confidence: 99%